ANALISIS KARAKTERISTIK HASIL PROSES PENGECORAN BESI COR KELABU DENGAN VARIASI DESIGN MODEL INTI COR - Sandy F Candra (Universitas Harapan Medan, 2019)
This study is a study that mengililasi casting process gray cast iron. From the characteristics obtained data table attached. Based on the results of research that the microstructure of the specimens in this study is the result of casting gray cast iron which has a strong and sturdy perlite metric. Graphite flakes in specimens I (3% Bentonite) were harder than specimens II (5% Bentonite). Ferrite in specimen I was more than ferrite in specimen II. Specimen I has a rather rough pearlite structure, while specimen II has fine pearlite. The hardness of gray cast iron possessed by 66.5 HRA II specimens was higher than that of gray cast iron possessed by specimen I which was 55.8 HRA. The tensile strength in specimens II was 278.68 N / mm2 higher than the tensile strength of specimens I was 222.92 N / mm2